Pulse Oximeter Manufacturing & Wireless Telemetry for Ventilation Oxygen Support - Ali Ihsan BÜLBÜL; Serdar KÜÇÜK (International Journal of Applied Methods in Electronics and Computers, 2016)
Pulse Oximeter devices are widely used as a non-invasive method for instant monitoring of blood oxygen saturation and heart rate. In this paper, a wireless microcontroller based pulse oximeter is proposed to measure the oxygen delivered to the patient via the oxygen flowmeter. In the first step, the signals received from reusable SpO 2 sensor (finger probe) are processed by a microcontroller to determine the blood oxygen saturation and heart rate. Depending on the current blood oxygen saturation value, wireless signals are sent to the non-invasive ventilation flow meter vacuum regulator to deliver the necessary oxygen into the patient. Oxygen supplied to the patient is automatically controlled according to the oxygen saturation change.